Changes in physicochemical, microbiological, and sensory quality of fermented milk with Lactiplantibacillus pentosus during cold storage - SUSMIATI SUSMIATI; SRI MELIA; ILFA KHAIRINA; HURRIYA ALZAHRA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Susmiati, Melia S, Khairina I, Alzahra H. 2024. Changes in physicochemical, microbiological, and sensory quality of fermented milk with Lactiplantibacillus pentosus during cold storage. Biodiversitas 25: 269-275. Fermented milk is a probiotic milk product created through a fermentation process that includes the addition of lactic acid bacteria, specifically Lactiplantibacillus pentosus. Enhancing the product's organoleptic qualities and extending its shelf life are the primary objectives of milk fermentation. This study aimed to determine the levels of protein, fat, water, pH value, TTA value, total lactic acid bacteria (LAB) colonies and sensory quality like taste, aroma and texture of fermented milk at 1, 7, 14, 21 and 28 days of storage. The results showed that protein content, fat content, water content, pH value, TTA value, and total colony LAB ranged from 5.30-6.96%, 6.01-7.49%, 72.03-88.89%, 4.78-5.17, 0.96-1.30%, 6.73-11.06 x109 CFU/mL, respectively . The overall organoleptic quality level was highest in the samples with the shortest storage time.